Effects of Atypical Antipsychotics on Neuroactive Vitamins in Patients With Schizophrenia. (19th May 2020) - Yuan, Tengfei; Wang, Shaoting; Le, Juan; Li, Yan
Abstract: In schizophrenia, neuroactive vitamins A/D/E play vital neuroprotective roles in its pathophysiological processes. During medical treatment, atypical antipsychotics, including aripiprazole, amisulpride, olanzapine, and paliperidone, were widely used at present. However, their impact on vitamin metabolism in vivo remained unclear. In this study, we conducted a case‐control research to investigate the impacts of antipsychotics on vitamin metabolism. Schizophrenic patients (n = 163), who were divided into 5 groups (aripiprazole group, amisulpride group, olanzapine group, paliperidone group, nonmedication group) according to their different medication patterns, and healthy controls (n = 75) were involved. The concentrations of vitamin A/D/E and antipsychotics were measured using liquid chromatography–tandem mass spectrometry methods. Compared with healthy controls, significantly lower vitamin D and E concentrations were found in the nonmedication group after covariance analysis adjusting for age, sex, albumin, bilirubin, triglyceride, and cholesterol. We found that aripiprazole could affect vitamin D concentrations in vivo, and a positive correlation between aripiprazole concentrations and vitamin D concentrations ( r = 0.319, P = 0.025) was observed in aripiprazole group. Such result revealed the very first observation for the influence of atypical antipsychotics medication toward vitamin status in vivo. Our study showed that low concentrations of vitamin D and E in vivo could be associated with schizophrenia, suggesting that hypovitaminosis may lead to a vulnerability to schizophrenia. More importantly, aripiprazole may potentially benefit the patients through improving their vitamin D status in vivo.